The Impact of Market Shocks on Cross-listed Companies : Company shares on the LSE and American Depositary Receipts on the NYSE or the NASDAQ during 2000-2017 - Ståhle, Mathias (My University, 2019)
The aim of this study is to find out what are the impacts of ten significant market shocks on cross-listed companies’ shares listed on the London Stock Exchange and American Depositary Receipts listed on the New York Stock Exchange or on the NASDAQ Stock Market during 2000—2017 and thus examine whether the markets are efficient or not. According to widely known theories, as the Law of One Price and the Efficient Market Hypothesis, all identical assets should have the same price and reflect all available information. Therefore, cross-listed companies’ shares and depositary receipts should react in a like manner when there is new information coming to the markets. Market shocks cause great turmoil on the markets and provide an excellent opportunity to test the theories in challenging circumstances. The best places to carry out the testing are naturally in the UK and in the U.S., due to their efficiency as well as popularity regarding to the cross-listing company structure. The data used in this study comes from the Thomson Reuters Datastream. All the 29 cross-listed companies selected for this study are well-known, multinational and financially strong firms. Event study method is used as a tool to measure the impacts of the market shocks on the prices of cross-listed shares and American Depositary Receipts. This way it is also possible to find out whether the markets are efficient or not. The analysis of the results obtained permits the evaluation of the possible price differences and their meaning. It is to be concluded that the market shocks have, on average, a negative impact on the prices of the shares and on the corresponding depositary receipts. The reaction is stronger among the shares then among the depositary receipts studied. The strongest reaction takes place on the very day when the new information reaches the markets and when the markets can react to it, which in turn, indicates that the markets are efficient. However, it is to be observed that this reaction lasts longer than expected which indicates that the markets are not efficient. A significant price difference between the shares and depositary receipts develops and this creates arbitrage opportunities during the time when the markets digest the new information. All kinds of market shocks have an impact, but a financial-type market shock has the strongest one. Different business industries are affected by the shocks and the effects differ between the industries.
Keywords: Cross-listing, market shock, American Depositary Receipt, market efficiency, VIX